Arabidopsis CALCIUM-DEPENDENT PROTEIN KINASE8 and CATALASE3 Function in Abscisic Acid-Mediated Signaling and H2O2 Homeostasis in Stomatal Guard Cells under Drought Stress. Issue 5 (12th May 2015) - Zou, Jun-Jie; Li, Xi-Dong; Ratnasekera, Disna; Wang, Cun; Liu, Wen-Xin; Song, Lian-Fen; Zhang, Wen-Zheng; Wu, Wei-Hua
Abstract : Arabidopsis CPK8 acts as a positive regulator in ABA-mediated plant responses to drought stress through regulation of CAT3 activity. Abstract: Drought is a major threat to plant growth and crop productivity. Calcium-dependent protein kinases (CDPKs, CPKs) are believed to play important roles in plant responses to drought stress. Here, we report that Arabidopsis thaliana CPK8 functions in abscisic acid (ABA )- and Ca 2+ -mediated plant responses to drought stress. The cpk8 mutant was more sensitive to drought stress than wild-type plants, while the transgenic plants overexpressing CPK8 showed enhanced tolerance to drought stress compared with wild-type plants. ABA -, H2 O2 -, and Ca 2+ -induced stomatal closing were impaired in cpk8 mutants. Arabidopsis CATALASE3 (CAT3) was identified as a CPK8-interacting protein, confirmed by yeast two-hybrid, coimmunoprecipitation, and bimolecular fluorescence complementation assays. CPK8 can phosphorylate CAT3 at Ser-261 and regulate its activity. Both cpk8 and cat3 plants showed lower catalase activity and higher accumulation of H2 O2 compared with wild-type plants. The cat3 mutant displayed a similar drought stress-sensitive phenotype as cpk8 mutant. Moreover, ABA and Ca 2+ inhibition of inward K + currents were diminished in guard cells of cpk8 and cat3 mutants. Together, these results demonstrated that CPK8 functions in ABA -mediated stomatal regulation in responses to drought stress through regulation of CAT3 activity.